The legal regime of digital assets in the context of European standards - S. O. Slipchenko; A. S. Slipchenko (Bulletin of Kharkiv National University of Internal Affairs)
The subject of the research is civil legal relations arising in relation to digital assets, with the chosen topic also defined. The aim of the research is to determine the compliance/non-compliance of the legal regime of digital assets established by Ukrainian legislation with the standards of European Union law. Using a comparative legal method, it is substantiated that the traditional domestic understanding of the legal regime of property fully aligns with European standards. This factor, considering the signed Association Agreement between Ukraine and the European Union, the need to harmonize national law with European standards, demonstrates the relevance and scientific novelty of the work.